2019
DOI: 10.3390/polym11122030
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Rubber Composites with High Breakdown Strength and Low Dielectric Loss Based on Polydopamine Coated Mica

Abstract: High breakdown strength and low dielectric loss are necessary for the outdoor insulator using silicone rubber (SR) composites. In this work, polydopamine coated mica (mica-PDA) was synthesized via bioinspired dopamine self-polymerization, and mica-PDA-filled SR composite (SR/mica-PDA-VTMS) was prepared using vinyl tri-methoxysilane (VTMS) as a silane coupling agent which serves as the molecular bridges between the organic rubber and the inorganic filler. The SR/mica-PDA-VTMS composite demonstrated dense and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…For DHNTs, there exist two peak components with the binding energy at 398.5 eV for N and 399.5 eV for NH, which were formed by the indole groups through structure evolution during the self‐polymerization of dopamine. [ 21,30 ] While for PEI‐DHNTs, an additional N1s peak at 400.7 eV could be found in the spectrum, which is related to NC due to the crosslinking between PEI and PDA. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For DHNTs, there exist two peak components with the binding energy at 398.5 eV for N and 399.5 eV for NH, which were formed by the indole groups through structure evolution during the self‐polymerization of dopamine. [ 21,30 ] While for PEI‐DHNTs, an additional N1s peak at 400.7 eV could be found in the spectrum, which is related to NC due to the crosslinking between PEI and PDA. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
“…For DHNTs, there exist two peak components with the binding energy at 398.5 eV for N and 399.5 eV for F I G U R E 1 (a) XPS survey scan spectra of HNTs, DHNTs, and PEI-DHNTs, (b) N1s spectra of DHNTs and PEI-DHNTs N H, which were formed by the indole groups through structure evolution during the self-polymerization of dopamine. [21,30] While for PEI-DHNTs, an additional N1s peak at 400.7 eV could be found in the spectrum, which is related to N C due to the crosslinking between PEI and PDA. [25] TGA was conducted to further confirm the deposition of organic layers on the surface of nanotubes.…”
Section: Characterization Of Dhnts and Pei-dhntsmentioning
confidence: 96%
“…With the development of UHV transmission technology, the reliability requirements for the electrical equipment in AC/DC transmission systems with different voltage levels have become more and more strict [ 1 , 2 , 3 ]. High-voltage high-power electronic devices (such as IGBT and IGCT) are the core components for manufacturing various high-voltage large-capacity power converters and control equipment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative filler materials including boron nitride (BN), mica, aluminum oxide, etc. have been sought to replace ATH in high voltage SR composite insulators [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating 7 wt.% thermally conductive BN particles in the SR composites, Du et al [20] found an improvement in the thermal dissipation and a decrease in both erosion depth and weight loss, indicating improved electrical erosion resistance. By the addition of mica modified by polydopamine and silane coupling agents, Liao et al [16] reported SR composites with~43% higher breakdown strength as compared to that of the ATH-filled SR composites. Aluminum nitride (AlN) is a thermally conductive material with a combination of good electrical insulation ability and low dielectric loss, which is desired for applications in high voltage insulation.…”
Section: Introductionmentioning
confidence: 99%